Learning functional programming with F♯ - Gumus, Onur (Packt Publishing, 2017)
"In today's world fully functional web applications are a key requirement and a necessity. We can have a run through developing web applications that includes server-side as well as the client-side programming using Fable, F♯ to JavaScript compiler. We will focus on the .NET Core platform so that your application will work in a cross-platform manner."--Resource description page